Cyber-attacks Based on Legal Requirements and International Relations of Governments - Maryam Sedaghat; Mojtaba Mireh Gini (Budapest International Research and Critics University, 2019)
Nowadays, the change in the scope of power from hard power to soft power has also shifted the process of military attacks to cyberattack. Cyber-attacks, like armed attacks, must fit into the framework of humanitarian law. Therefore, government responsibilities are also determined based on these changes, and as governments have responsibilities in military strikes, their responsibilities for cyberattacks should also be identified. Therefore, the present study makes use of analytical-descriptive method based on existing documents to examine this issue. Ultimately, the present study concludes that a cyberattack could be described as armed use of force in accordance with Article 2 (4) of the United Nations Charter. On the other hand, a widespread cyberattack on the basic infrastructures that causes material damages or casualties comparable to an armed attack with conventional weapons, gives the affected government the right to seek legitimate defense. Also, governments can resort to legitimate defense in response to a cyberattack that does not amount to an armed attack but provides the settings for an impending armed attack with conventional weapons.